Toward a Theory of Human Rights : Religion, Law, Courts - Perry, Michael J (Cambridge University Press, 2013)
This book has three parts. Part One (Chapters 1 –3) is about the morality of human rights; Part Two (Chapters 4–7), about the relation of the morality of human rights to the law of human rights; and Part Three (Chapters 8–9), about the proper role of courts in protecting the law of human rights.